Speeding Up Optimum-Path Forest Training by Path-cost Propagation - Iwashita, Adriana S. [UNESP]; Papa, Joao P. [UNESP]; Falcao, Alexandre X.; Lotufo, Roberto A.; Araujo Oliveira, Victor M. de; Costa de Albuquerque, Victor H.; Tavares, Joao Manuel R. S.; IEEE (Ieee, 2012)
In this paper we present an optimization of the Optimum-Path Forest classifier training procedure, which is based on a theoretical relationship between minimum spanning forest and optimum-path forest for a specific path-cost function. Experiments on public datasets have shown that the proposed approach can obtain similar accuracy to the traditional one hut with faster data training.